Can China Think? - Anne Cheng (Collège de France, 2013)
Since the Age of Enlightenment in Europe, much scholarly work has been done on "thinking China". A result has been the most contradictory representations which attempt to reconcile "philosophical China" with "Oriental despotism", or an eternal aesthetic and consensual China with a more unpredictable and disturbing vision of the country. To break free of these tenacious clichés, Anne Cheng proposes that we listen carefully to what Chinese authors actually have to say. After all, is China not h...